2022
DOI: 10.3390/mi13101648
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fin Shape on the Heat Transfer and the Solution Time of a Microchannel Evaporator in a CO2 Air Conditioning System—A Numerical Investigation

Abstract: Numerical simulations on the fin shape of a microchannel evaporator in a CO2 air conditioning system were performed at the inlet evaporative temperature of 10 °C and the vapor quality of 0.61. Two types of fin shapes were dealt with: the straight fins and V-fins. The numerical results were verified by the experimental data. For the system under consideration and for the same heat transfer area and the heat transfer coefficient for the air side in the microchannel evaporator, the effect of the fin shape on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It is widely used in the comparative analysis of engineering field [ 27 ]. Nguyen, T. [ 28 ] selected the k–e turbulence model to study the effects of the straight fins and V–fins on the numerical simulation results of heat dissipation. The research showed that the effect of the fin shape on the heat transfer was not different when other conditions are equal.…”
Section: Performance Analysis Based On Cfd Simulationmentioning
confidence: 99%
“…It is widely used in the comparative analysis of engineering field [ 27 ]. Nguyen, T. [ 28 ] selected the k–e turbulence model to study the effects of the straight fins and V–fins on the numerical simulation results of heat dissipation. The research showed that the effect of the fin shape on the heat transfer was not different when other conditions are equal.…”
Section: Performance Analysis Based On Cfd Simulationmentioning
confidence: 99%
“…This model was solved based on Conjugate Heat Transfer model [17,18], which was formed of two models: (1) Heat Transfer in Solids and Fluids and (2) Turbulent Flow.…”
Section: Numerical Simulationmentioning
confidence: 99%